Instrument for Protection and Enforcement of Human Rights in Indonesia - Rizky Ahadyan Ardyansyah; Saiful Rizal (Rechtenstudent, 2023)
Human rights are an inseparable component of human life, both in the social, economic, religious, political and even educational fields, because these rights are an integral part of every human being since birth. In addition, the context of the discussion of Human Rights cannot be separated from the scope of the state, because it has become an obligation for a country to guarantee and protect this right under any conditions, Indonesia is also one of the countries that provide guarantees and protection for every right. human rights, although in reality its implementation can still be categorized as not conducive, because this can be seen in the development of cases that allude to the issue of upholding human rights in Indonesia. During the reform era in Indonesia, there were several amendments to the 1945 Constitution. These amendments aimed to improve and strengthen the democratic system and protect human rights. In 1999, the first amendment was made to the 1945 Constitution. This research aims to find out the basic legal concept of protecting and enforcing human rights law in Indonesia, besides that it also aims to increase public insight into the importance of human rights values in the context of state life. In this research the author uses a normative approach by examining several materials or literature data which also discusses the issue of basic legal concepts of protection and enforcement.